PEMANFAATAN LIMBAH PLASTIK MENJADI KEMASAN RAMAH LINGKUNGAN SERTA UJI BIODEGRADASINYA - Asiska Permata Dewi; Yulia Yesti (LPPM Universitas Abdurrab, 2018)
Manufacturing of prototype of plastics film for a biodegradable packaging from a mixture of polymer synthetic polystyrene (PS) and polycaprolactone (PCL) has been carried out. Plastics film containing of PS/PCL created by blending techniques followed by solvent casting, the ratios were 100/0, 95/5, 90/10 and 85/15. The resulting of plastic film is a clear sheet with an average thickness of 0.03 cm. The biodegradation rate profile was observed by soil burial test method to see the weight reduction of the plastic films tested for a certain period of time. The results showed that the biodegradation rate profile increased with the addition of PCL with the t50% in the 100/0, 95/5, 90/10 and 85/15 ratios respectively being 352.33; 91.19; 71.97 and 59.85 weeks, and t95% in the 100/0, 95/5, 90/10 and 85/15 ratios were respectively 677.01; 177.32; 139.43 and 115.79 weeks. Furthermore, the number of microbes present in each gram of soil is 1.83 x 105.